Gemar Gatra Traditional Gymnastics Training to Improve Physical Fitness of High School Students in Eastern - Suryani, Sri; Artanayasa, I Wayan; Swadesi, I Ketut Iwan; Semarayasa, I Ketut; Lesmana, Kadek Yogi Parta (LPPM Undiksha, 2025)
There are still many students who still need to improve their physical fitness. Students who are too lazy to exercise have an impact on their poor health. This study aims to analyze the effect of Gemar Gatra gymnastics training on improving students' physical fitness. This study is a quantitative study with a quasi-experimental approach. The study sample sample was 40 male students in grade XI of high school. The method used in data collection was a questionnaire and test. The research instrument used was the Indonesian Physical Fitness Test (TKJI) for males aged 16-19 years. The data analysis technique can be used to test hypotheses using ANOVA. The results of the study showed that Gemar Gatra gymnastics training had a significant effect on improving students' physical fitness. The paired Sample T-Test test showed a significant difference between students' physical fitness before and after participating in Gemar Gatra gymnastics training. It was concluded that Gemar Gatra gymnastics can improve students' physical fitness. This study implies that Gemar Gatra gymnastics training can be used for high school students. The implications of the research are that Gemar Gatra gymnastics exercises can be applied by teachers so that they can improve students' physical fitness.